Sesquiterpene Synthases of Zanthoxylum ailanthoides : Sources of Unique Aromas of a Folklore Plant in Taiwan - Chuang, Chun-Wei; Wen, Chi-Hsiang; Wu, Tsai-Jung; Li, Ching-Ching; Chiang, Nien-Ting; Ma, Li-Ting; Ho, Chen-Lung; Tung, Gene-Sheng; Tien, Chin-Cheng; Lee, Yi-Ru; Chu, Fang-Hua (Journal of agricultural and food chemistry, 2021)
is a traditional spice crop in Taiwan with unique smells and tastes that differ between prickly (young) and nonprickly (mature) leaves. Different volatile terpenes between prickly young and nonprickly mature leaves were identified and considered to be one of the sources of their aromas. A transcriptome database was established to explore the biosynthesis of these compounds, and candidate terpene synthase genes were identified. The functions of these synthases were investigated using recombinant protein reactions in both purification and coexpression assays. TPS1, TPS2, and TPS3 are germacrene D synthases, with different amino acid sequences. The main products of TPS4 are α-bergamotene and ( )-β-farnesene, whereas TPS5 forms multiple products, and TPS6 produces β-caryophyllene. TPS7 forms monoterpene ( )-β-ocimene and sesquiterpene ( , )-α-farnesene. Reverse transcription PCR of gene expression in young and mature leaves revealed that TPS1 was responsible for the mellow aroma in mature leaves. The expression of TPS6 suggested that it plays a role in the background aromas of both types of leaves. Our findings deepened the understanding of the volatile compounds of and revealed the source of its unique aromas by clarifying the biosynthesis of these compounds.